Ejecución del presupuesto público y percepción de la gestión del Gobierno Regional de Loreto en el periodo 2014 – 2023 - Grandez Paz, Ronier (2024)
This research examines the relationship between the execution of the public budget and the perception of the management of the Regional Government of Loreto during the period 2014-2023. Using a quantitative approach with a correlational level and non-experimental cross-sectional design, budget execution data and citizen perception surveys were analyzed. Through Spearman's rating coefficient, a significant positive rating was identified between efficiency in budget execution, both in activities and projects, and a favorable perception of government management. The results suggest that efficient financial administration, together with effective execution of activities and projects visible to the community, improves citizen perception. However, the study also reveals the influence of other contextual and socioeconomic factors, such as poverty and security, that affect public opinion. The conclusions highlight the importance of comprehensive public management that combines budget efficiency with communication, transparency and social development strategies. The recommendations and proposals developed seek to optimize resource management and strengthen public trust, thus promoting more effective governance and sustainable development in the Loreto region.